The impact of spikes in handgun acquisitions on firearm-related harms - Hannah S. Laqueur; Rose M. C. Kagawa; Christopher D. McCort; Rocco Pallin; Garen Wintemute (BMC, 2019)
Abstract Background Research has documented sharp and short-lived increases in firearm acquisitions immediately following high-profile mass shootings and specific elections, increasing exposure to firearms at the community level. We exploit cross-city variation in the estimated number of excess handgun acquisitions in California following the 2012 presidential election and the Sandy Hook school shooting 5 weeks later to assess whether the additional handguns were associated with increases in the rate of firearm-related harms at the city level. Methods We use a two-stage modeling approach. First, we estimate excess handguns as the difference between actual handgun acquisitions, as recorded in California's Dealer Record of Sales, and expected acquisitions, as predicted by a seasonal autoregressive integrated moving-average (SARIMA) time series model. We use Poisson regression models to estimate the effect of city-level excess handgun purchasing on city-level changes in rates of firearm mortality and injury. Results We estimate there were 36,142 excess handguns acquired in California in the 11 weeks following the election (95% prediction interval: 22,780 to 49,505); the Sandy Hook shooting occurred in week 6. We find city-level purchasing spikes were associated with higher rates of firearm injury in the 52 weeks post-election: a relative rate of 1.044 firearm injuries for each excess handgun per 1,000 people (95% CI: 1.000 to 1.089). This amounts to approximately 290 (95% CI: 0 to 616) additional firearm injuries (roughly a 4% increase) in California over the year. We do not detect statistically significant associations for shorter time windows or for firearm mortality. Conclusion This study provides evidence for an association between excess handgun acquisitions following high-profile events and firearm injury at the community level. This suggests that even marginal increases in handgun prevalence may be impactful.